Formation of stages of management of intellectual property in an industrial enterprise - Maslak, M. V. (My University, 2023)
Under the concept of “intellectual property management”, it is proposed to understand an integrated system of training and providing various levels of management for effective planning, control and management decision-making regarding intellectual property objects. It is designed to ensure the coordination, interaction and consistency of individual management elements to achieve the strategic goals of the enterprise and its effective operation.
Формування етапів управління інтелектуальною власністю на промисловому підприємстві
Keywords: intellectual property; management; coordination; efficiency; strategic goals